A Study of Mutual Funds from Different Sectors in India - Agarwal, Sonali; Tandon, Chand; Raychaudhuri, P. S. (Indian Journal of Research in Capital Markets, 2015)
Savings constitute a major part of GDP in India. These savings flow into different investment avenues. People commit their funds in expectation of some future returns in terms of revenue or capital. The main hurdle in this process is the selection of the appropriate security which involves complete market and security analysis along with portfolioÂ management. This becomes a difficult task for ordinary investors, given their busy life. This leads the investors to resort to indirect methods of investing, the most prominent and successful being the mutual funds which manage the portfolio on behalf of the investors. However, the selection of the correct mutual fund is an important task. The present study attempted to analyze and compare a few selected mutual funds to help the investors in fund selection.